A Profile of Adult Severe Acute Respiratory Syndrome Coronavirus 2 Pneumonia Patients According to Pneumococcal Vaccination Status - María Morales-Suárez-Varela; Diana Toledo; María Amelia Fernández-Sierra; María Liébana; Gerardo Rubiera; Gema Navarro; Concepción Prados; Judith Chamarro; Isabel Peraita-Costa; Angela Domínguez; Working Group of Project FIS PI19/00354 (Vaccines, 2023)
Certain patient profile characteristics, such as preexisting medical conditions, can modify the risk of developing SARS-CoV-2 pneumonia among adults vaccinated and not vaccinated against pneumococcal disease. This retrospective cohort study aimed to quantify the risk of pneumonia caused by SARS-CoV-2 among individuals from 15 to 64 years old with and without pneumococcal vaccination in Spain during the 2020–2021 influenza season and establish a risk profile of patients more likely to develop SARS-CoV-2 pneumonia. Data (demographic information, patient medical history, and lifestyle habits) were gathered both directly from the patient via personal interview and by reviewing electronic medical records. In an adjusted analysis for pneumococcal vaccinated patients, visits to hospital outpatient clinics were protective while visits to primary health care services, being widowed, obese, and not using masks in outdoor open spaces were identified as risk factors. For patients who had not received a pneumococcal vaccine, visits to hospital outpatient clinics were protective, while being overweight or obese, alcohol consumption, and not using masks in outdoor open spaces were identified as risk factors. Concerning comorbidities, in the pneumococcal vaccinated group none were found to be protective but having diabetes or other respiratory diseases were identified as risk factors. In the unvaccinated group, undergoing immunosuppressive treatment and having metastatic tumors were protective factors, while cerebrovascular disease and obesity with a BMI ≥ 40 were risk factors. A similar risk profile for developing SARS-CoV-2 pneumonia in pneumococcal vaccinated and non-vaccinated individuals was found. Generally, vaccinated individuals had a lower risk of developing SARS-CoV-2. The findings suggest that vaccination against S. pneumoniae could prevent and reduce SARS-CoV-2 pneumonia. Additionally, this study has identified individuals with other medical conditions, such as obesity, underweight, diabetes, and a history of respiratory diseases, who are at an increased risk of developing SARS-CoV-2 pneumonia and could benefit from vaccination and supervision.